SETTLER SUBURBIA IN THE NEGEV/NAQAB: THE START-UP PIONEER IN THE DESERT. - Adolfsson, Johanna (Geographical Review, 2024)
Within the recognized borders of Israel, in the shadow of the West Bank settlement enterprise, a new frontier is in the making. Central planning has designated the space as a burgeoning metropolitan region, and, in a parallel process, a network of Jewish-only settlements has been established. This study asks how the settlement push is narrated to the Israeli public, and thereby adds the Naqab to previous studies exploring the link between colonial settlement and suburbia, and more specifically with the community-settlement model. It analyzes audiovisual material produced by two Zionist organizations and finds that the new frontier is narrated as a space for reenactment of the mythic pioneer trope, and that this ideal is mediated in relation to the new neoliberal ethos of Israel as the "start-up nation." The study moreover expands on the interplay of geographic scales, thus adding an important contribution to scholarly understanding of contemporary settler-colonialism.